The Role of School Climate Perception on Teaching Efficacy with Special Needs Children : Examining Teachers' Perspective in Kota Depok - Anisa Rahmadani; Muhammad Yudi Ali Akbar; Zahrina Amelia (Muslim Education Review, 2025)
This study is grounded in the premise that prior to delving into teachers' perspectives on inclusive education implementation, it is imperative to possess a tool that assesses their confidence in teaching children with special needs. Employing a quantitative methodology, the research investigates the correlation between demographic variables, perceptions of school climate, and the effectiveness of teaching children with special needs. 72 teachers from public and private schools in Kota Depok were involved in this research. This research aims to address the question, does perceived school climate impact teaching efficacy for children with special needs? Using a t-test and regression analysis, this research found a significant association between teachers' perceptions of an inclusive school climate and their efficacy in instructing students with special needs. Moreover, the regression analysis underscores the predominant role of school-provided resources, collaboration, and instructional innovation in shaping teaching efficacy.